Engineering Education Based on Integration with Science and Industry - Yu. M. Kazakov; N. Yu. Bashkirtseva; M. V. Zhuravleva; G. O. Ezhkova; A. S. Sirotkin; A. O. Ebel (Высшее образование в России)
The development of globalization processes requires the provision of scientific and technological leadership of economies. In solving this goal, universities are called upon to play a special role, which can ensure the competitiveness of engineering education. Among the main indicators of academic leadership are ensuring the world level of training content, increasing academic mobility, growing demand and efficiency of master's and postgraduate studies, increase in the number of online educational programs, increase in the number of competitive courses and programs taught online, development of a targeted training system. The key condition for increasing the competitiveness of engineering education is the strengthening of its integration with science and the industrial sector. This is due to the possibility of solving a set of tasks for the development of content, organization and management of the educational process. The effectiveness of their solution is determined by the composition of partners involved in joint activities. The analysis shows that there are trends in the expansion of partnerships and the intensification of international cooperation. This facilitates the development of various formats of interaction to improve the training of engineers. Among the most developing integrated forms of training are networked educational programs. A distinctive feature of their implementation is the growth in the number of participants in network partnerships, among them are universities (as a rule more than one), industry institutes, enterprises (more than one). The network format is being implemented and remains promising in the organization of student practices. The basic departments created at enterprises are the main instrument of targeted training. With the development of the system of professional standards, the role of integration of universities with enterprises in organizing and conducting procedures for assessing the qualifications of personnel has increased. The need to solve the problem of increasing the global competitiveness of education reinforces the requirement to develop the integration of universities with academic science in the form of scientific and educational centers, with foreign universities, enterprises and high-tech businesses.